The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1093/infdis/jiaa338
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Seasonal Influenza Attack Rates and Antibody Dynamics in Children Using Cross-Sectional Serological Data

Abstract: Abstract Directly measuring evidence of influenza infections is difficult, especially in low surveillance settings such as sub-Saharan Africa. Using a Bayesian model, we estimated unobserved infection times and underlying antibody responses to influenza A/H3N2 using cross-sectional serum antibody responses to four strains in children aged 24-60 months. Among the 242 individuals, we estimated a variable seasonal attack rate and found that most children had at leas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…However, many milder cases (including outpatients) are included in the reports as they may seek healthcare at the hospital, thereby increasing the expected reporting rate in this context. Overall therefore, our model estimates fit the data well, as well as known aspects of influenza and RSV transmission, such as high influenza attack rates in children 31,32 , and higher RSV severity in the youngest children 33 .…”
Section: Discussionsupporting
confidence: 54%
“…However, many milder cases (including outpatients) are included in the reports as they may seek healthcare at the hospital, thereby increasing the expected reporting rate in this context. Overall therefore, our model estimates fit the data well, as well as known aspects of influenza and RSV transmission, such as high influenza attack rates in children 31,32 , and higher RSV severity in the youngest children 33 .…”
Section: Discussionsupporting
confidence: 54%
“…There is limited information on the attack rate of seasonal HCoV, however there have been numerous studies looking at influenza. Previous systematic reviews have estimated the attack rate of influenza to be between 3.5% and 22.5% [26][27][28] , whilst modelling studies have estimated this to be higher, 20 -60% 29,30 . Based on reporting rates of seasonal HCoV we would expect the attack rate to be lower than influenza.…”
Section: Discussionmentioning
confidence: 99%
“…There is little information on the attack rate of HCoVs, but there have been several systematic reviews and meta-analyses looking at unvaccinated individuals which have reported the attack rate to range between 15.2% -22.5% in children and 3.5% -10.7% in adults [26][27][28] . Modelling studies using serological influenza data predicted estimates from 20 -60% 29,30 . We expect the attack rate for HCoV may be lower based on the epidemiology of these viruses in children 31 , but we selected a prior which covers a range of plausible values.…”
Section: Methodsmentioning
confidence: 99%
“…However these were not greatly different, with the medians of the two priors only differing by 3.6% and therefore not substantially different to help us distinguish between the two modes. Overall therefore, our model estimates fit the data well, as well as known aspects of influenza and RSV transmission, such as high influenza attack rates in children [46,47], and higher RSV severity in the youngest children [48].…”
Section: Discussionmentioning
confidence: 83%